Immunoreactivity of a Monoclonal Antibody to SS18-SSX Fusion Gene Product in Formalin-fixed Paraffin-embedded Synovial Sarcoma Tissue Section. Issue 3 (March 2018) - Saigo, Chiemi; Kito, Yusuke; Takeuchi, Tamotsu
Abstract : Synovial sarcoma is an aggressive sarcoma with specific reciprocal chromosomal translocation of SS18 (also known as SYT ) and SSX genes. In the present study, we aimed to detect the SS18-SSX fusion gene product in routinely processed pathologic synovial sarcoma tissue section. Monoclonal antibodies to peptide QRPYGYDQ-IMPKKPA, which covered the fusion region of SS18-SSX, were newly established and subsequently characterized by enzyme-linked immunosorbent assay, Western-immunoblotting, and immunohistochemical staining. A monoclonal antibody designated BG35, reacted with boundary region of SS18-SSX chimera protein in a specific manner, when C-terminal or neighboring region of QRPYGYDQ-IMPKKPA is structurally exposed. Immunoreactivity of BG35 was localized in nucleus of synovial sarcoma cells, but not in other sarcoma cells, examined. Interestingly, synovial sarcoma cells with epithelial differentiation exhibited much strong BG35 immunoreactivity than synovial sarcoma cells with sarcomatous differentiation. BG35 may be useful for evaluating molecular kinetics of SSX-SS18 gene product in situ.